The importance of endogenous capacities and government support in the resilience of regions - Ayda Eraydin (European Regional Science Association (ERSA), 2014)
The importance of endogenous capacities and government support in the resilience of regions The paper aims to discuss the major determinants that make a region more resilient than the other regions and the role of government policies in building resilient regions. It aims to explore both the endogenous factors and government policies and support for regional resilience that enable regions to respond and recover from economic crisis conditions. Therefore, the paper focuses three major questions: How do different regions react to economic crises? Why do some regions manage to overcome the negative conditions created by the economic volatilities and adapt to new conditions, recover or even make use of the new conditions for innovative restructuring, while the others do not? What is the importance of government policies that enables regions to cope with and recover from economic crisis? The paper presents theoretical argumentation on these questions and the case study that identifies the different levels of resilience of Turkish regions and the compares the importance of endogenous capacities and government support both in recession and recovery periods of the economic crisis in Turkey.
Keywords: 330; resilience; adaptive capacity; government policies